2002
DOI: 10.1142/s021773230200717x
|View full text |Cite
|
Sign up to set email alerts
|

Reducibility and Bosonization of Parasupersymmetric and Orthosupersymmetric Quantum Mechanics

Abstract: Order-p parasupersymmetric and orthosupersymmetric quantum mechanics are shown to be fully reducible when they are realized in terms of the generators of a generalized deformed oscillator algebra and a Z p+1 -grading structure is imposed on the Fock space. The irreducible components provide p + 1 sets of bosonized operators corresponding to both unbroken and broken cases. Such a bosonization is minimal.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…(1) and (2) by considering occupancy of neutron h 11/2 orbital. As in the reference [44], it was shown that the interactions of order higher than 2 are important in the 0f 7/2 shell for f p shell nuclei. In our case for Te isotopes, with 2 protons outside Z = 50 core, there is no contribution of three-body…”
Section: Estimate For Contributions From Three-body Forcessupporting
confidence: 53%
See 1 more Smart Citation
“…(1) and (2) by considering occupancy of neutron h 11/2 orbital. As in the reference [44], it was shown that the interactions of order higher than 2 are important in the 0f 7/2 shell for f p shell nuclei. In our case for Te isotopes, with 2 protons outside Z = 50 core, there is no contribution of three-body…”
Section: Estimate For Contributions From Three-body Forcessupporting
confidence: 53%
“…It may also shift the individual states different way. The importance of three-body forces for lighter nuclei were reported in literature [44,45,46,47,48]. The average energy shift of states with n valence particles due to a 3N force can be written as…”
Section: Estimate For Contributions From Three-body Forcesmentioning
confidence: 98%
“…The two corresponding eigenspaces F 0 and F 1 , made of even or odd number states, respectively, are such that F = F 0 ⊕ F 1 , the corresponding projectors being P 0 = 1 2 (1 + T ) and P 1 = 1 2 (1 − T ). On starting from the general results obtained for order-p parasupersymmetric quantum mechanics in [24] and setting p = 1, which gives back SUSYQM, we arrive at two different realizations of superalgebra (15) in terms of the GDOA (27), namely…”
Section: Bosonization In Terms Of a Gdoamentioning
confidence: 99%
“…In such a framework, SUSYQM turns out to be fully reducible, its irreducible components providing two sets of bosonized operators realizing either broken or unbroken SUSYQM. Such an approach in terms of GDOAs was latter on applied [24,25,26] to several variants of SUSYQM, namely parasupersymmetric [27,28,29], orthosupersymmetric [30], pseudosupersymmetric [31], and fractional supersymmetric quantum mechanics [32].…”
Section: Introductionmentioning
confidence: 99%
“…In the q‐deformed theory we have a famous q‐deformed exponential functions called Jackson's q‐exponential function which is defined by 0trueeqJ(x)=n=01false[nfalse]!xnwhere q‐number is defined as [n]q=qn1q1The Jackson's q‐exponential function obeys xqeqJfalse(xfalse)=eqJfalse(xfalse)where Jackson's q‐derivative was defined as xqFfalse(xfalse)=F(qx)F(x)x(q1)Acting the Jackson's q‐derivative on monomials yields xqxn=[n]qxn1The Jackson's q‐derivative was used in the study of q‐deformed bosonic system and several investigators have studied the equilibrium statistical mechanics of the gas of non‐interacting q‐boson systems …”
Section: Introductionmentioning
confidence: 99%